Predictors of Leadership Capacities on Administrative Effectiveness among Secondary School Principals in Kebbi State, Nigeria - Ibrahim, Musa; Shittu , Rasheedat Badamasi (Kashere Journal of Education, 2025)
Effective school leadership is globally recognised as a driver of school improvement and administrative efficiency. In Kebbi State, Nigeria, secondary schools continue to face significant leadership and governance challenges, often resulting in low educational outcomes. This study was conducted to examine the relationship between leadership capacities—such as strategic vision, team building, conflict management, decision-making, staff supervision, and motivation and the administrative effectiveness of secondary school principals in Kebbi State. A correlational survey design was utilised, encompassing 176 secondary school principals chosen via stratified random sampling. Data were collected using a structured questionnaire and analysed using descriptive statistics, zero-order Pearson correlations, and standard multiple regression techniques. Each leadership dimension was treated as an independent variable, while administrative effectiveness was the dependent variable. The results indicated that all leadership dimensions were positively related to administrative effectiveness, meaning that as each leadership quality improved, so did administrative effectiveness: strategic vision (r = .38, p < .001), team building (r = .34, p < .001), conflict management (r = .35, p < .001), decision making (r = .30, p < .001), staff supervision (r = .26, p = .001), and motivation The multiple regression model was statistically significant, F (6, 169) = 7.07, p < .001, and accounted for 20.1% of the variance in administrative effectiveness (R² = .20). Among the predictors, only strategic vision (β = .25, p = .010) and conflict management (β = .22, p = .016) significantly predicted administrative effectiveness. The study concludes that strategic planning and effective conflict resolution are the most influential leadership capacities for achieving administrative success in the study context. It is recommended that principal selection and development programs emphasise these critical areas